2011
DOI: 10.1590/s0102-311x2011000200012
|View full text |Cite
|
Sign up to set email alerts
|

Alimentação complementar e estado nutricional de crianças menores de dois anos atendidas no Programa Saúde da Família em Acrelândia, Acre, Amazônia Ocidental Brasileira

Abstract: Com objetivo de investigar o estado nutricional e alimentação complementar em crianças de 6 a 24 meses, residentes na Amazônia Ocidental Brasileira, um estudo transversal foi realizado na área urbana do Município de Acrelândia, Estado do Acre, com 164 crianças. As prevalências de déficit de estatura/idade e anemia foram de 12% e 40%, respectivamente, e de deficiência de ferro isolada, de 85%. Os níveis séricos das vitaminas A e B12 estavam baixos em 15% e 12% das crianças, respectivamente. Houve baixo consumo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
1
34

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 27 publications
7
35
1
34
Order By: Relevance
“…This scenario is in agreement with that observed in the most recent surveys [10][11][12][21][22][23][24] and with nationwide studies [25][26][27][28][29][30][31] as well as with those undertaken in other Latin American countries [3][4][5][6][7] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This scenario is in agreement with that observed in the most recent surveys [10][11][12][21][22][23][24] and with nationwide studies [25][26][27][28][29][30][31] as well as with those undertaken in other Latin American countries [3][4][5][6][7] .…”
Section: Discussionsupporting
confidence: 92%
“…Other studies conducted in various regions of the country [25][26][27][28][29] found prevalences of stunting greater than those of this study, with a variation of from 6.7% (in children of 10 years of age in the city of Ferros, Minas Gerais, in the southeast of Brazil) 27 to 12.3% (in children of 6 to 24 months of age resident in Acrelândia, in the State of Acre, in northern Brazil) 28 .…”
Section: Discussioncontrasting
confidence: 66%
“…A baixa ingestão de frutas, verduras de folhas, legumes e carnes se repercute na baixa ingestão de micronutrientes e, por consequência, nas deficiências nutricionais. Estudo realizado na Região Norte, no Município de Acrelândia, no Acre, investigou as condições de saúde e nutrição de crianças com idade entre 6-24 meses e confirmou que a dieta ingerida por estas não supria as necessidades diárias de ácido fólico, vitamina C, vitamina A, zinco e ferro, conforme recomendadas para essa faixa etária 23 . Apesar da qualidade da dieta das crianças residentes nas regiões Norte e Nordeste estarem muito aquém do recomendado, estudo demonstrou que a desnutrição infantil na Região Nordeste reduziu em cerca de 50%, no período compreendido entre 1996 e 2006 (13,5% para 6,8%).…”
Section: Síntese Do Consumo Por Região De Residênciaunclassified
“…The size of the sample was calculated using the Epi Info TM software, taking into account an estimate that 50% of children show inadequate feeding practices (9)(10)(11)(12) ; a population of 3,904 children under the age of three, registered in the PHCs; a confidence level of 95%; and a margin of error of 5%. The calculation showed the need for 350 motherchild pairs.…”
Section: Introductionmentioning
confidence: 99%